Perception of affordances for vertical and horizontal jumping in children: gymnasts versus non-athletes - Peker, A. T.; Erkmen, N.; Kocaoglu, Y.; Bayraktar, Y.; Arguz, A.; Wagman, J. B.; Stoffregen, T. A. (Research Quarterly for Exercise and Sport, 2021)
Purpose: We investigated the perception of affordances for vertical jumping-and-reaching and horizontal jumping by children.